2016
DOI: 10.36076/ppj/2016.19.e1041
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Thermocoagulation Radiofrequency Treatment of the Ophthalmic Division (V1) and/or Maxillary (V2) and Mandibular (V3) Division in Idiopathic Trigeminal Neuralgia: An Observational Study

Abstract: Background: Trigeminal neuralgia (TN) is a pain appearing in the ophthalmic (V1), maxillary (V2), and mandibular (V3) trigeminal branches. Pharmacologic treatment is the first line for TN; however, many patients prefer to receive minimally invasive treatment rather than medicine because of intolerable side effects. Thermocoagulation radiofrequency (TRF) is a minimally invasive treatment that has been shown to effectively treat the maxillary (V2) and mandibular (V3) divisions, but the safety of TRF treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In their systematic review of the efficacy and safety of percutaneous approaches in the management of TN, Texakalidis et al emphasized that when solely targeting the maxillary division, 31 it was difficult to contain the thermocoagulatory damage from reaching the ophthalmic or mandibular divisions and its real-time detection. [31][32][33] Tang et al in their study, which enrolled older patients above 70 years of age, reported an excellent pain relief in all their patients at discharge, with 49% maintaining pain relief even after 10 years. 34 Zhao et al in their RF series of 1,070 patients reported a pain-free rate in 70.2% of the patients at 10 years and reported that patients prone to long-term pain recurrence are those having initial poor response to medications, patients with atypical facial pain, and patients with previous facial numbness.…”
Section: Discussionmentioning
confidence: 94%
“…In their systematic review of the efficacy and safety of percutaneous approaches in the management of TN, Texakalidis et al emphasized that when solely targeting the maxillary division, 31 it was difficult to contain the thermocoagulatory damage from reaching the ophthalmic or mandibular divisions and its real-time detection. [31][32][33] Tang et al in their study, which enrolled older patients above 70 years of age, reported an excellent pain relief in all their patients at discharge, with 49% maintaining pain relief even after 10 years. 34 Zhao et al in their RF series of 1,070 patients reported a pain-free rate in 70.2% of the patients at 10 years and reported that patients prone to long-term pain recurrence are those having initial poor response to medications, patients with atypical facial pain, and patients with previous facial numbness.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, postoperative side effects such as facial swelling, facial numbness, ecchymosis, hematoma at puncture site, eye injury, blindness or infection were also recorded. The degree of facial numbness was scored as follows: 27 0: no numbness; 1: mild numbness (with no significant impact on life); 2: moderate numbness (with some impact on life); and 3: severe numbness (intolerable).…”
Section: Methodsmentioning
confidence: 99%
“…The objective of improving both clinical outcomes and safety has promoted a shift in the treatment strategy in percutaneous RFTC for TN from intracranial localization to selective extracranial localization of individual divisions [ 12 ]. The transfer of interventional targets from the intracranial ganglion to the extracranial trigeminal nerve has been reflected in recent studies that used the extracranial within-FO approach to selectively destroy the MN [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%